Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.bbamcr.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled receptor GPR19 regulates E-cadherin expression and invasion of breast cancer cells

Abstract: Dysregulation of G protein-coupled receptors (GPCRs) is known to be involved in the pathogenesis of a variety of diseases, including cancer initiation and progression. Within this family, approximately 140 GPCRs have no known endogenous ligands and these "orphan" GPCRs remain poorly characterized. The orphan GPCR GPR19 was identified and cloned 2 decades ago, but relatively little is known about its physio-pathological relevance. We observed its expression to be elevated in breast cancers and therefore sought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 47 publications
4
61
0
Order By: Relevance
“…5). Elevated ERK expression has been detected in various human tumours, such as ovarian, colon, breast and lung cancer (85)(86)(87)(88). Denkert et al (89) found that the expression of MAPK phosphatase-1 (MKP-1) in normal ovarian surface epithelium and benign cystadenomas is increased compared to invasive carcinomas and low malignancy potential tumors and borderline tumors.…”
Section: Erk/mapk Signalling Pathway and Tumorigenesismentioning
confidence: 99%
“…5). Elevated ERK expression has been detected in various human tumours, such as ovarian, colon, breast and lung cancer (85)(86)(87)(88). Denkert et al (89) found that the expression of MAPK phosphatase-1 (MKP-1) in normal ovarian surface epithelium and benign cystadenomas is increased compared to invasive carcinomas and low malignancy potential tumors and borderline tumors.…”
Section: Erk/mapk Signalling Pathway and Tumorigenesismentioning
confidence: 99%
“…Stein et al found that in rats, adropin suppresses water intake via activation of GPR19 in the brain [5]. Moreover, it was found that adropin modulates E-cadherin expression in breast cancer cells via activation of GPR19 [6]. In addition, another study reported that adropin modulates pyruvate dehydrogenase in cardiac cells in a GPR19-dependent manner [7].…”
Section: Discovery Of Adropin and The Adropin Receptormentioning
confidence: 99%
“…Several studies found that adropin and its putative receptor GPR19 may be involved in the biology of cancer cells. GPR19 mRNA is high in human breast carcinoma [6]. Furthermore, overexpression of GPR19 in mesenchymal-like breast cancer stimulates E-cadherin expression and promotes the epithelial-like phenotype via the MAPK/ERK1/2 pathway [6].…”
Section: Adropin and Cancermentioning
confidence: 99%
“…The in vitro invasion assay was performed essentially as previously described by Rao et al (9). Briefly, stably transected MCF7 cells (5 3 10 5 cells per chamber) were plated in DMEM onto the upper compartment of the invasion chamber, and DMEM was added to the lower compartment.…”
Section: Matrigel Invasion Assaymentioning
confidence: 99%
“…One alternative approach is to target the pharmacologically tractable membrane receptors transmitting the extracellular signals that regulate intracellular signaling pathways. GPCRs, the largest family of cell surface-signaling molecules, have emerged as critical players in cancer metastasis (8), and our previous work has demonstrated that GPCR expression can affect cancer cell phenotype (9,10). Given the fact that ;50-60% of all current therapeutic agents target GPCRs directly or indirectly (11), targeting GPCR signaling may represent a viable approach for the treatment of breast cancer metastasis.…”
mentioning
confidence: 99%